Non-Financial Performance Measurement for Shariah Banks: A Surbey to Masyarakat Ekonomi Syariah (MES) Surakarta - Septian Puji Astuti, Hari Astika (ITB, 2011)
Measurement of non-financial performance in shariah banks is needed to enhance their market share and to maintain their long-team sustainability. The main aim of this research is to show the position or shariah banks in Surakarta in respect with their non-financial aspects (i.e. product, service, human resource and image) based on opinions given by members of Shariah Economic Society (MES) of financial performance of the banks. The result inicates that the first two banks with best non-finance performance ar BMI and BSM